The Cost of a Family - Henderson, A. M. (Review of Economic Studies, 1949)
Journal Article The Cost of a Family Get access A. M. Henderson A. M. Henderson Manchester Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 17, Issue 2, 1949, Pages 127–148, https://doi.org/10.2307/2295869 Published: 01 January 1949